2021
DOI: 10.3390/molecules26051495
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adherence to Antihypertensive Medication by Means of Dose-Dependent Reference Plasma Concentration Ranges and Ultra-High Performance Liquid Chromatography-Ion Trap Mass Spectrometry Analysis

Abstract: Poor adherence to antihypertensive drug therapy is a well-recognized problem and can be assessed by mass spectrometry-based analyses of body fluids. However, contrary statements exist whether drug quantification in blood or qualitative screening in urine is more suitable. The present pilot study aimed to further elucidate the power of blood plasma drug concentrations for adherence monitoring by developing and validating a quantification procedure for nine antihypertensive drugs (amlodipine, bisoprolol, candesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
2
0
3
Order By: Relevance
“…In terms of clinical application, analysis of drug concentrations in blood serum is useful in detecting patient nonadherence to antihypertensive medication. Many recent studies found high rates of non-adherence to antihypertensive therapies which prompt simple and reliable monitoring of medication adherence with special attention to at-risk groups of patients [ 28 , 29 , 30 , 31 , 32 ]. Meantime, AML is the perfect first-line medicine available in a single fixed-dose combination form for different cardiovascular diseases with excellent pharmacokinetic parameters [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical application, analysis of drug concentrations in blood serum is useful in detecting patient nonadherence to antihypertensive medication. Many recent studies found high rates of non-adherence to antihypertensive therapies which prompt simple and reliable monitoring of medication adherence with special attention to at-risk groups of patients [ 28 , 29 , 30 , 31 , 32 ]. Meantime, AML is the perfect first-line medicine available in a single fixed-dose combination form for different cardiovascular diseases with excellent pharmacokinetic parameters [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Измерение концентрации ЛС в крови является перспективным практическим подходом в оценке комплаенса и адаптации доз и схем лечения для отдельных пациентов. Высокоэффективная жидкостная хроматография с масс-спектрометрией (ВЭЖХ/МС) -это объективный высокоточный и широко используемый метод терапевтического мониторинга лекарственных препаратов, который привлек внимание исследователей к оценке приверженности лечению у пациентов с высоким сердечно-сосудистым риском [8][9][10].…”
Section: терапевтический лекарственный мониторинг для оценки комплаен...unclassified
“…Пациенты с уровнями сывороточной концентрации по крайней мере 1 прописанного АГП ниже минимального предела обнаружения считаются неприверженными лечению. Именно такой методологический подход используется для оценки приверженности пациентов с АГ антигипертензивной терапии [10]. Разработка таких методик в исследовании на небольшой выборке пациентов с АГ (n=91) показала, что при качественном анализе (положительные/отрицательные) доля неприверженных составляла 6,6%, тогда как использование количественного анализа до пороговых значений концентраций позволяет более точно выявлять долю неприверженных пациентов до 19,8% [9].…”
Section: терапевтический лекарственный мониторинг для оценки комплаен...unclassified
See 1 more Smart Citation
“…Hereby, assessing adherence based on blood concentrations with individually calculated lower dose-related concentrations (DRC) is more accurate than using qualitative analysis alone [11,12]. Up to date, several LC-MS methods for the quantification of AHD exist [13][14][15][16] but they are based on blood, plasma, or serum needing venipuncture, which can cause discomfort and anxiety and requires healthcare professionals. With dried blood spots (DBS), an alternative to venipuncture is known since 1963 [17].…”
Section: Introductionmentioning
confidence: 99%